Splice factor mutations and alternative splicing as drivers of hematopoietic malignancy. Issue 1 (January 2015) - Hahn, Christopher N.; Venugopal, Parvathy; Scott, Hamish S.; Hiwase, Devendra K.
Summary: Differential splicing contributes to the vast complexity of mRNA transcripts and protein isoforms that are necessary for cellular homeostasis and response to developmental cues and external signals. The hematopoietic system provides an exquisite example of this. Recently, discovery of mutations in components of the spliceosome in various hematopoietic malignancies (HMs) has led to an explosion in knowledge of the role of splicing and splice factors in HMs and other cancers. A better understanding of the mechanisms by which alternative splicing and aberrant splicing contributes to the leukemogenic process will enable more efficacious targeted approaches to tackle these often difficult to treat diseases. The clinical implications are only just starting to be realized with novel drug targets and therapeutic strategies open to exploitation for patient benefit.